2017
DOI: 10.9734/ijpss/2017/33722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Viruses Infecting Sorghum in Nigeria-A Review

Abstract: Viruses infecting sorghum are widely distributed in Asia and Africa and are of economic importance. In recent years, apparent virus disease incidence has increased, probably due to changes in agricultural practices associated with the introduction of hybrids and new varieties that are being developed and released continuously. The first virus disease described on sorghum in the world was Sugarcane mosaic virus (SCMV). Nigeria is one of the leading sorghum producing countries in the world and most of its popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…Thrips and whiteflies were also found to be associated with diseased cowpea plants this is consistent with the reports of [28] that whiteflies are vectors of cowpea mosaic virus and is also supported by the reports of several authors [29,30]. Aphids and leafhoppers were also found in association with diseased maize plants agreeing favourably with the reports of several authors [31,32] who both reported that Aphids and Leafhoppers are vectors of maize mosaic disease. [33] reported that the main vectors of the okra mosaic virus were Aphids and whiteflies, these two arthropods were also found to be associated with the diseased okra plants sampled in this research.…”
Section: Mean Incidence Of Viral Symptoms On Cropssupporting
confidence: 90%
“…Thrips and whiteflies were also found to be associated with diseased cowpea plants this is consistent with the reports of [28] that whiteflies are vectors of cowpea mosaic virus and is also supported by the reports of several authors [29,30]. Aphids and leafhoppers were also found in association with diseased maize plants agreeing favourably with the reports of several authors [31,32] who both reported that Aphids and Leafhoppers are vectors of maize mosaic disease. [33] reported that the main vectors of the okra mosaic virus were Aphids and whiteflies, these two arthropods were also found to be associated with the diseased okra plants sampled in this research.…”
Section: Mean Incidence Of Viral Symptoms On Cropssupporting
confidence: 90%